FOXOs and their roles in acute and chronic neurological disorders - Asadi, Yasin; Moundounga, Rozenn K.; Chakroborty, Anand; Pokokiri, Augustina; Wang, Hongmin (Frontiers in Molecular Biosciences, 2025)
The forkhead family of transcription factors of class O (FOXOs) consisting of four functionally related proteins, FOXO1, FOXO3, FOXO4, and FOXO6, are mammalian homologs of daf-16 in Caenorhabditis elegans and were previously identified as tumor suppressors, oxidative stress sensors, and cell survival modulators. Under normal physiological conditions, FOXO protein activities are negatively regulated by phosphorylation via the phosphoinositide 3-kinase (PI3K)-Akt pathway, a well-known cell survival pathway: Akt phosphorylates FOXOs to inactivate their transcriptional activity by relocalizing FOXOs from the nucleus to the cytoplasm for degradation. However, under oxidative stress or absent the cellular survival drive of growth factors, FOXO proteins translocate to the nucleus and upregulate a series of target genes, thereby promoting cell growth arrest and cell death and altering mitochondrial homeostasis. FOXO gene expression is also regulated by other transcriptional factors such as p53 or autoregulation by their activities and end products. Here we summarize the structure, posttranslational modifications, and translocation of FOXOs linking to their transcriptional control of cellular functions, survival, and death, emphasizing their role in regulating the cellular response to some acute insults and chronic neurological disorders. This review will conclude with a brief section on potential therapeutic interventions that can be used to modulate FOXOs’ activities when treating acute and chronic neurological disorders.